HVOF Diamalloy 2002 coating of steel surface: electrochemical corrosion resistance. Issue 2 (9th March 2015) - Yilbas, B. S.; Toor, I.-H.; Patel, F.; Al-Shehri, Y.; Baig, M. A.
Abstract : Purpose: – The purpose of this paper is to investigate the corrosion resistance of high velocity oxy-fuel (HVOF)-sprayed Diamalloy 2002 coating on carbon steel. The coating microstructure is examined in line with the corrosion resistance. Design/methodology/approach: – HVOF spraying of coating is achieved, and the coating response to electrolytic solution is measured experimentally in terms of corrosion resistance. Findings: – HVOF coating improves the corrosion resistance of the substrate such that the corrosion rate of the substrate is 7.1 mpy and the coating results in 4.5 mpy. However, presence of deep pit sites at the surface suggests the occurrence of preferential corrosion around the splat boundaries. In addition, closely spaced surface texture peaks act as crevice corrosion centers at the surface while initiating the formation of deep pit sites. Research limitations/implications: – This study is limited by experimental investigations. In future, it may be extended to include model studies. Practical implications: – The findings of this study are very useful for those working in the coating industry. However, HVOF coating is limited to high temperature protection in harsh environments. Social implications: – It is useful for the power industry, particularly for gas turbines. Originality/value: – It is an original work and describes the corrosion resistance of the coating surface. It is found that the coating improved the corrosion resistance of the steel surface.